Design, Synthesis, Molecular Docking and In silico Analysis of Some Novel 2-Amino-1, 3, 4-Thiadiazole Derivatives as Potent DNA Gyrase B Inhibitors - Ramalakshmi, Natarajan; A., Prabakaran; S., Sumithra; S., Keerthika; J., Nivetha; R., Raveena (Current Bioactive Compounds, 2021)
Introduction: Thiadiazole derivatives have been reported as a potent antimicrobial agent and the discovery of drug molecules for antimicrobial-resistant strains of Escherichia coli is still a vital challenge in the modern world. Objective: The objective of the present study is to design, synthesize and perform molecular docking studies and in-silico analysis of some novel 2-amino-1, 3, 4-thiadiazole derivatives with the aim of developing potential DNA gyrase B inhibitors. Materials and Methods: The compound 5-substituted-1, 3,4-thiadiazol-2-amine derivatives [compound 1a-1c] ; 5,6-Diphenyl- 2-[5-(substituted)-1,3,4-thiadiazol-2-yl amino]-2H -1,2,4-triazine- 3-thione derivatives [compound 2a-2c]; and propyl 3,4,5-trihydroxy-2,6-bis [5-(substituted)- 1,3,4-thiadiazol-2-yl amino] benzoate derivatives [compound 3a -3c] were synthesised by temperature- controlled microwave-assisted method. The structures of the synthesized compounds were drawn in ChemSketch. Further, molecular docking and in-silico studies for the prediction of druglikeness, pharmacokinetic parameters and prediction of toxicity were carried out . The structures of the synthesized compounds were characterized by FT-IR, 1H NMR and mass spectral analysis. Results: The synthesized compounds had a better yield.The docking studies of the synthesized compounds had a better docking score with a good binding affinity towards the protein molecule. The synthesized compounds also comply with the in-silico prediction of drug-likeness, pharmacokinetic parameters and prediction of toxicity. Conclusion: The present study reveals that the 5-substituted-1, 3,4-thiadiazol-2-amine derivatives can serve as a better lead as potent DNA gyrase B inhibitor in further drug discovery.",
Keywords: in-silico analysis